Clio's southern sisters : interviews with leaders of the Southern Association for Women Historians - Schulz, Constance B.; Turner, Elizabeth Hayes (Southern women., 2004)
"It is no accident that the Southern Association for Women Historians enjoys the founding date of 1970. After extended and often bitter engagement with entrenched sexism in the decades following World War II, women historians found their voices and crafted a means by which to be heard. The years between 1970 and 1980 represented a decade of optimism for women who sought equality in the workplace. Professional women, professors of history most especially, found hope in organizations such as the SAWH, created to address issues of visibility, legitimacy, and equality in historical associations and in employment." "In Clio's Southern Sisters, Constance B. Schulz and Elizabeth Hayes Turner collect the stories of the women who helped to found and lead the organization during its first twenty years. These women give evidence, in strong and effective language, of the experiences that shaped their entree into the profession. They describe the point at which they experienced the shift in their lives and in the lives of those around them that led toward a new day for women in the history profession."--Jacket.